The Grapes of Wrath Movie Still - Twentieth Century Fox:::Creator::::::::::::
Tom Joad (Henry Fonda) and Pa Joad (Russell Simpson) trying to convince Grandpa Joad (Charley Grapewin) to leave the homestead while the family looks on in Twentieth Century Fox's adaptation of John Steinbeck's novel. RESTRICTED USE